2007
DOI: 10.3758/bf03194070
|View full text |Cite
|
Sign up to set email alerts
|

Simon says: Reliability and the role of working memory and attentional control in the Simon task

Abstract: The Simon effect refers to the observation that subjects identify targets (e.g., colors) faster when the irrelevant spatial location of the target corresponds to the location of the response key. Theoretical accounts of the Simon effect typically explain performance in terms of automatic and controlled processes. Furthermore, the relative contributions of automatic and controlled processes are held to change as a function of the proportion of compatible to incompatible trials (compatibility proportion). Data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…This study sets itself within the context of a long series of studies of control processes in conflict paradigms, derived primarily from the Gratton et al (1992) study (although this study had its precursors in the work of Logan and Zbrodoff in the late 1970s; Logan & Zbrodoff, 1979). This and other work has shown that (1) the modulation of the flanker effect is not due solely to response repetition effects (see Experiment 3 in Gratton et al [1992] and Verbruggen, Notebaert, Liefooghe, & Vandierendonck [2006] for examples), contradicting earlier conclusions from Mayr, Awh, and Laurey (2003), but is a form of adaptive control; (2) adaptive control can be location and item specific (see Blais, Robidoux, Risko, & Besner, 2007;Corballis & Gratton, 2003; see also Jacoby, Lindsay, & Hessels, 2003;Jacoby, McElree, & Trainham, 1999;Trainham, Lindsay, & Jacoby, 1997); (3) adaptive control is related to stimulus rather than response conflict (Notebaert & Verguts, 2006;Verbruggen et al, 2006); (4) adaptive control in conflict paradigms can be considered in terms of the relative utilization of automatic and controlled processing (Borgmann, Risko, Stolz, & Besner, 2007), following a gating mechanism; and (5) adaptive control can be conceptualized as a form of Hebbian learning (Verguts & Notebaert, 2008; see also Braver & Cohen, 2001).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This study sets itself within the context of a long series of studies of control processes in conflict paradigms, derived primarily from the Gratton et al (1992) study (although this study had its precursors in the work of Logan and Zbrodoff in the late 1970s; Logan & Zbrodoff, 1979). This and other work has shown that (1) the modulation of the flanker effect is not due solely to response repetition effects (see Experiment 3 in Gratton et al [1992] and Verbruggen, Notebaert, Liefooghe, & Vandierendonck [2006] for examples), contradicting earlier conclusions from Mayr, Awh, and Laurey (2003), but is a form of adaptive control; (2) adaptive control can be location and item specific (see Blais, Robidoux, Risko, & Besner, 2007;Corballis & Gratton, 2003; see also Jacoby, Lindsay, & Hessels, 2003;Jacoby, McElree, & Trainham, 1999;Trainham, Lindsay, & Jacoby, 1997); (3) adaptive control is related to stimulus rather than response conflict (Notebaert & Verguts, 2006;Verbruggen et al, 2006); (4) adaptive control in conflict paradigms can be considered in terms of the relative utilization of automatic and controlled processing (Borgmann, Risko, Stolz, & Besner, 2007), following a gating mechanism; and (5) adaptive control can be conceptualized as a form of Hebbian learning (Verguts & Notebaert, 2008; see also Braver & Cohen, 2001).…”
Section: Discussionmentioning
confidence: 58%
“…Although there is considerable evidence that motor patterns can be learned without intention and explicit knowledge, there is much less evidence that the same is true for adaptive control processes. This is particularly the case because the phenomena underlying adaptive control appear to be related to the weighting of different types of information (related to automatic vs. controlled processing), rather than merely to the speed with which different processes occurs (see Borgmann et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The Simon effect, defined as the average of the reaction times in the incongruent trials minus the average of the reaction times in the congruent trials, is the outcome measure that will be reported. The Simon Task has reliability coefficients ranging from 0.56 to 0.65 (Borgmann, Risko, Stolz, & Besner, 2007).…”
Section: Inhibitory Controlmentioning
confidence: 99%
“…This can result in a considerable diminution of the interference effect or even its disappearance (e.g., Kane and Engle, 2003). In some cases, the effect can even reverse and congruent trials yield longer RTs than incongruent trials (e.g., Borgmann et al, 2007;Leboe and Mondor, 2008;Merikle and Joordens, 1997). Whether crosstalk interference reduces, disappears or reverses is likely to depend on the relative strength of the conflict between relevant and irrelevant stimuli/responses on the one hand, and the processing advantage afforded by semantic predictability on the other hand.…”
Section: Discussionmentioning
confidence: 96%